The Reconstruction of Islamic Law in Indonesia: From Classical Fiqh to Nusantara Fiqh - Muhammad Syauqi Arinalhaq; Sholahuddin Al Ayubi; Andi Rosa (Medina-te : Jurnal Studi Islam, 2026)
The rapid development of modern civilization and the complex social dynamics in Indonesia call for a change in the application of Islamic law. Deeply ingrained in ancient fiqh literature, the ideas of Islamic law often expose flaws in handling the complexity of modern dynamics, especially in the multicultural setting of Indonesia. This study aims to clarify the relevance of reconstructing Islamic law in line with the setting of fiqh inside the archipelago since it answers the problems of the modern day. And to critically analyze the dynamics of Islamic legal thought in Indonesia in responding to contemporary reality challenges through a reconstructive approach to classical fiqh towards Nusantara fiqh. Specifically, this research focuses on how local scholars reformulate fiqh principles in the context of Indonesia's pluralistic and dynamic social, political, and cultural landscape. Examining a range of ancient fiqh studies, the viewpoints of Nusantara academics, and contemporary debates in the field of Islamic law, this paper uses a library research technique and a qualitative-descriptive method. The results of this discussion show that Nusantara fiqh is more than just local adaptation of classical fiqh; rather, it is a contextual ijtihad process combining local knowledge, social reality, and the basic values of maqāḥid al-syarī'ah. With the existence of Nusantara fiqh, it enables a more inclusive, adaptive, and relevant Islamic law in reconstructing Islamic law itself according to the needs of Indonesian society in the modern era without neglecting the principles of Islamic Shari'ah itself. Therefore, this article explains the importance of a reform in Islamic law that can adapt to contemporary dynamics while still being rooted in authoritative Islamic scholarly principles.